Challenging Traditional Islamic Authority: Indonesian Female Ulama and the Fatwa Against Forced Marriages - Agustina, Arifah Millati; Ismah, Nor (Institut Agama Islam Negeri (IAIN) Pontianak, 2024)
Forced marriage practices have garnered significant attention from various international communities, including the community of female ulama in Indonesia. Despite being a relatively new presence, the community of female ulama affiliated with the Congress of Indonesian Female Ulama (KUPI) has taken a decisive stance against this practice, issuing a firm fatwa (Islamic legal opinion) that underscores its detrimental impact on women. This article addresses the primary question of why female ulama associated with KUPI redefine the concept of wilāyāt al-ijbār (compulsory guardianship) in marriage, departing from the prevailing opinion among traditional Islamic scholars. Through a combination of literature review and field research conducted over eight months, spanning from April to November 2022, this study reveals that KUPI interprets ijbār not as the paternal right to force a daughter into marriage, but rather as a form of guardianship that entails responsibility and nurturance towards their daughter. This fatwa framework is rooted in what is termed the ‘KUPI Trilogy’: ma‘rūf (good), mubādalah (reciprocity), and keadilan hakiki (substantive justice), which promote principles of equality and egalitarianism. By employing theological, sociological, and juridical arguments and emphasizing the experiences of female victims, KUPI contends that the concept of wilāyāt al-ijbār in fiqh (Islamic jurisprudence) is not absolute, thereby prohibiting guardians from coercing or intimidating their daughters into marriage. This article argues that female ulama have boldly contested the authority of traditional ulama by reinterpreting the essence of ijbār in fiqh, while incorporating the lived experiences of female victims of forced marriage practices. [Praktik perkawinan paksa telah menarik perhatian serius dari berbagai komunitas internasional, termasuk komunitas ulama perempuan di Indonesia. Meskipun relatif baru, komunitas ulama perempuan yang tergabung dalam Kongres Ulama Perempuan Indonesia (KUPI) ini mengeluarkan fatwa tegas yang menentang praktik ini, menyoroti dampak buruknya terhadap perempuan. Artikel ini menjawab pertanyaan utama mengapa ulama perempuan yang tergabung dalam KUPI merekonstruksi konsep ijbār wali dalam perkawinan secara berbeda dengan mayoritas pendapat ulama fikih tradisional. Melalui kombinasi penelitian pustaka dan lapangan selama delapan bulan, mulai dari April hingga November 2022, penelitian ini mengungkap bahwa KUPI menginterpretasikan makna ijbār bukan sebagai hak paksa wali untuk menikahkan anak perempuannya, melainkan sebagai bentuk tanggung jawab dan kasih sayang wali terhadap putrinya. Pendekatan fatwa ini didasarkan pada konsep Trilogi KUPI, yaitu ma‘rūf, mubādalah, dan keadilan hakiki, yang menawarkan semangat kesetaraan dan egaliter. Dengan mengadopsi argumen teologis, sosiologis, dan yuridis dengan menekankan pengalaman korban perempuan, KUPI berpendapat bahwa konsep ijbār wali dalam fikih tidak bersifat mutlak, sehingga wali dilarang memaksa atau mengintimidasi anak perempuannya untuk menikah. Artikel ini berargumen bahwa ulama perempuan telah berani menantang otoritas ulama tradisional dengan merekonstruksi makna ijbār dalam fikih, dengan melibatkan pengalaman korban perempuan terkait praktik perkawinan paksa.]